Frankbaronia velata nov. sp., a putative peronosporomycete oogonium containing multiple oospores from the Lower Devonian Rhynie chert - Harper, Carla (My University, 2013)
Spherical to pyriform microfossils containing multiple smooth-walled spherules from the Lower Devonian Rhynie chert are described as oogonia of a new fossil peronosporomycete based on congruencies in basic morphology to the polyoosporous oogonia of certain extant Saprolegniales. Because the new fossils also resemble Frankbaronia polyspora, a putative peronosporomycete described previously from the Rhynie chert, they are assigned to the fossil genus Frankbaronia and formally proposed as a new species, F. velata. Surrounding the oogonium is a conspicuous sheath of consolidated mucilage, produced and secreted by the oogonium during development. The discovery of F. velata adds to our understanding of the microbial diversity in early terrestrial ecosystems, and contributes to the documentation of the evolutionary history of the Peronosporomycetes.
PUBLISHED
Keywords: Mucilage sheath; Oomycota; Polyoosporous oogonium; Saprolegniales; Smart & Sustainable Planet; DEVONIAN; FOSSIL; Fossil Fungi; Fossils; MICROFUNGI; Oomycota; Rhynie chert